Spontaneous perforation of a primary duodenal diverticulum stepped treatment model: A 10-patient case report - Zhong, Bin; Li, Zhonghu; Lin, Zhenyu; Shen, Yanbing; Zhang, Jianxin; Jin, Weidong (Frontiers in Surgery, 2022)
After colonic diverticula, a duodenal diverticulum (DD) is the second most common type of gastrointestinal diverticulum. DD is mainly caused by poor congenital development, resulting in a limited outward protrusion of the duodenal wall in a sac (primary diverticula). Perforation is one of the infrequent but most severe complications of DD, most commonly in the second segment of the duodenum (D2, 58%), followed by the third segment (D3, 30%). In the current case reports on the treatment of DD perforation, preoperative diagnosis is rare, with most patients being diagnosed and treated by laparotomy; the surgical approach is complex and varied, with artificial choices; and there is a high rate of complications and mortality (6%–34%) after surgical treatment. This study aimed to review our experience treating spontaneous perforation of the primary duodenal diverticulum, focusing on the surgical treatment model. A retrospective review of all spontaneous perforations of primary DD was conducted at one center between January 2010 and January 2022. We identified 10 patients with spontaneous perforation of primary DD (6 women and 4 men; median age: 51.5 years; range: 24–87 years). The patients had a median American Society of Anesthesiologists (ASA) score of 2. All patients underwent surgical treatment, of which six had percutaneous retroperitoneal drainage, two had diverticulectomy, one had distal gastrectomy + gastrojejunostomy + diverticuloplasty, and one had diverticulum repair. No patients died. The median length of stay was 12 days (range: 3–21 days). There were no long-term complications during the follow-up period (median follow-up of 12 months). A stepwise treatment model for spontaneous perforation of primary DD appears to have more advantages, and transabdominal exploratory surgery should probably not be the preferred treatment modality.